O menino contador de histórias : a criança e a arquitetônica do ato narrativo - Oliveira, Marina de (2022)
The human being is a subject that is constituted by language and appropriates it to tell its own story. Children from an early age are entering this world of narrative that allows them to reconstruct their experiences, to give new meaning to them. This dissertation thematizes the architectonics of the child's narrative act. There were selected records, previously collected, available in the collection of the interinstitutional research group NALíngua (Nucleus for Studies in Language Acquisition)-CNPq. Therefore, this research has as its thematic delimitation the architectonics of the child's narrative act from 2nd to 5 years old. The investigation is justified because it seeks to understand the architectonics of the child’s narrative act, in which the child is observed as a singular subject. The problem that we seek to answer is: What principles govern the architectonic of the child's narrative act as a singular subject? So, the general objective of this research is to identify and analyze the principles that govern the architectural of the child's narrative act as a singular subject. To achieve this objective, Bakhtin's reflections mainly the ones presented in the work Para uma filosofia do ato responsável (2020) are mobilized, in addition to studies on Bakhtinian production, such as those by Sobral (2019, 2020) and Faraco (2009). The work explores the concepts of responsible act, non-alibi and subject based on a main theorical-philosophical construct: the architectonics of the responsible act, from which we derived the architectonics of the narrative act. The research can be delimited as exploratory, in terms of its objectives, as well as bibliographical and as a case study, in terms of technical procedures, in addition to being written based on qualitative aspects of the narrative research. The Phenomenological Study of the Narrative Act is used as a methodological proposal derived from reflections on phenomenology, from theoretical considerations of Bakhtin's work and in line with the specificity of this research. In addition, the main concepts of the research are considered from the Bakhtinian theoretical-philosophical basis, since this study is based on a main theoretical-philosophical construct: From the theoretical study and from the methodological definitions, four categories of analysis are delimited and help us to describe the transcribed the segments of the records of GUS available in the NALingua collection. The study of the data leads us to determinate five principles that govern the architectonics of the child’s narrative act: the constitutive interrelation, the space of the narrator child, the constitutive tension, the intonation as a mark of the child’s singularity and the process of apprehension of linguistic resources for spatiotemporal construction. Such elements lead to the inference that the child’s narrative act takes place in the interaction between one self and an other through linguistic resources that reconstruct and re-signify the lived experience.